Residual CO2 imaged with X‐ray micro‐tomography - Iglauer, Stefan; Paluszny, A.; Pentland, C.; Blunt, M. (American Geophysical Union, 2011)
Carbon capture and storage (CCS), where CO2 is injected into geological formations, has been identified as an important way to reduce CO2 emissions to the atmosphere. While there are several aquifers worldwide into which CO2 has been injected, there is still uncertainty in terms of the long‐term fate of the CO2. Simulation studies have proposed capillary trapping – where the CO2 is stranded as pore‐space droplets surrounded by water – as a rapid way to secure safe storage. However, there has been no direct evidence of pore‐scale trapping. We imaged trapped super‐critical CO2 clusters in a sandstone at elevated temperatures and pressures, representative of storage conditions using computed micro‐tomography (μ‐CT) and measured the distribution of trapped cluster size. The clusters occupy 25% of the pore space. This work suggests that locally capillary trapping is an effective, safe storage mechanism in quartz‐rich sandstones.